Comparative Evaluation of ICDAS, WHO and Histological Examination in Detection of Occlusal Carious Lesions - Alaa, Eman; El-Messiry, Hend (Brazilian Dental Science, 2020)
Detection of occlusal carious lesions with visual scoring systems is in a continuous validation with the histological depth of carious demineralization. Objective: The present study aimed to compare the International Caries Detection and Assessment System (ICDAS), the World Health Organization (WHO) system and histological examination in detecting occlusal carious lesions. Material and Methods: 20 premolars were evaluated by visual examination using ICDAS, WHO and histological examination using stereomicroscope (SM) for occlusal caries detection. Occlusal surfaces were evaluated by two examiners then all teeth were visually and histologically assessed. Results: For each of three systems the inter class correlation coefficient was examined, the differences between the three systems of occlusal caries detection were minimal. The visual examination through WHO recorded the higher intercorrelation coefficient followed by ICDAS system then histological examination respectively. Conclusion: WHO and ICDAS have demonstrated reproducibility and diagnostic accuracy when compared with histological examination for detecting occlusal caries. Keywords International caries detection and assessment system; World health organization; Histological examination; Occlusal caries.